PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi pada Perusahaan Biro Perjalanan PT. ZULINDO TOUR DI JALAN VETERAN 14 SEMARANG) - Diah Husnul Walidah, 07.05.51.0125; Sutino, Sutino (Students Journal of Economic and Management, 2012)
Customer satisfaction can only be formed if the customer was satisfied with the service received. The purpose of this study was to examine the effect of reliability, responsiveness, assurance and empathy for customer satisfaction PT Zulindo Tour. The population in this study were all customers of PT Zulindo Tour Veteran road no. 14 Semarang in the period 2010 and 2011 as many as 38 companies / schools. Sampling was done by using the withdrawal of nonprobability sampling design is by using purposive sampling is the sampling technique based on certain considerations. The consideration is the customer who never uses more than 2x PT Zulindo Tour. The samples that meet these criteria are 13 companies / schools. Each company / school divided the questionnaire as much as 5 copies. Techniques of data analysis using multiple linear regression analysis. The analysis concluded that: the positive effect of service quality to customer satisfaction. The better the quality of service, then customer satisfaction will increase Key words: quality of service and customer satisfaction